Intracerebroventricular administration of a modified hexosaminidase ameliorates late-stage neurodegeneration in a GM2 mouse model. - Manuel E Lopez; Daniel Wendt; Roger Lawrence; Kerui Gong; Hoonsan Ong; Bryan Yip; Joseph Chen; Linley Mangini; Britta Handyside; Alexander Giaramita; Aashish Lamichhane; Melanie Lo; et al. (PLoS ONE)
The GM2 gangliosidoses, Tay-Sachs disease and Sandhoff disease, are devastating neurodegenerative disorders caused by β-hexosaminidase A (HexA) deficiency. In the Sandhoff disease mouse model, rescue potential was severely reduced when HexA was introduced after disease onset. Here, we assess the effect of recombinant HexA and HexD3, a newly engineered mimetic of HexA optimized for the treatment of Tay-Sachs disease and Sandhoff disease. Enzyme replacement therapy was administered by repeat intracerebroventricular injections in Sandhoff disease model mice with dosing beginning before and after signs of neurodegeneration. As previously observed, HexA effectively increased the lifespan of Sandhoff disease mice by 3.5-fold only when treatment was started before onset of neurodegeneration. In contrast, HexD3 halted motor decline and ameliorated late-stage disease severity even when dosing began late, after neurodegeneration onset. Additionally, HexD3 had advantages over HexA in enzyme stability, distribution potential, and homodimer activity. Overall, our data indicate that advanced therapeutics may widen the treatment window for neurodegenerative disorders.